THE REALITY OF DIGITAL SOCIETY IN THE 21st CENTURY - Apdillah, Dicky; Elza Ms, Muhammad Fadli; Simanjuntak, Angelina Deasyta; Sihombing, M Hafiz Nurhasan; Nadeak, Bill Yansen (Transpublika Publisher, 2022)
We can see that digital technology is increasing rapidly year after year, and we also know that technology has become a significant part of our everyday lives for a variety of reasons, including work, school, leisure, and a variety of other activities. As a result, many individuals with non-digital jobs are losing their jobs at an alarming rate as they are replaced by technology. As a practical matter, we must be able to balance our technical capabilities in order for them to survive in the future. On the other hand, this quick development has both a positive and a negative impact on us. It has a beneficial impact on us, but it also has a detrimental impact on us. Hence , the author is interested in discussing and conducting research on